DFT and EPR Study of Spin Excitations in Oxidized Thiophene-Based Conjugated Oligomers - Victor Krinichnyi (Advanced Energy Conversion Materials, 2024)
Comparison of data obtained using the density functional theory (DFT) and electron paramagnetic resonance (EPR) method made it possible to establish the composition and state of spin charge carries in the poly(3, 4-ethylenedioxythiophene) (PEDOT) and poly(3-alkylthiophene) (P3AT) oligomers. The coexistence of several polarons on the P3AT chain, the properties of which are governed by the structure of the substituents, is identified. All terms of the spin Hamiltonians of different oligomers were obtained, and their high-resolution EPR spectra were calculated. The structure of the P3AT substituents is shown to influence the polaron spin state and hyperfine interaction with its own microenvironment. The prospects of the approaches used in the work to develop electronic and spintronic elements with spin-controlled parameters are shown.